miR-146a in Myasthenia Gravis Thymus Bridges Innate Immunity With Autoimmunity and Is Linked to Therapeutic Effects of Corticosteroids - Bortone, Federica; Scandiffio, Letizia; Marcuzzo, Stefania; Bonanno, Silvia; Frangiamore, Rita; Motta, Teresio; Antozzi, Carlo; Mantegazza, Renato; Cavalcante, Paola; Bernasconi, Pia (Frontiers in Immunology, 2020)
Toll-like receptor (TLR)-mediated innate immune responses are critically involved in the pathogenesis of myasthenia gravis (MG), an autoimmune disorder affecting neuromuscular junction mainly mediated by anti-acetylcholine receptor antibodies. Considerable evidence indicates that uncontrolled TLR activation and chronic inflammation significantly contribute to hyperplastic changes and germinal center formation (GC) in MG thymus, ultimately leading to autoantibody production and autoimmunity. Mir-146a is a key modulator of innate immunity, whose dysregulation has been associated with autoimmune diseases. It acts as inhibitor of TLR pathways, mainly by targeting the NF-κB signaling transducers IRAK1 and TRAF6; mir-146a is also able to target c-REL, ICOS and FAS, known to regulate B cell function and GC response. Herein, we investigated the miR-146a contribution to the intra-thymic MG pathogenesis. By real-time PCR, we found that miR-146a expression was significantly downregulated in hyperplastic MG compared to control thymuses; contrariwise, IRAK1, TRAF6, c-REL and ICOS mRNA levels were up-regulated and negatively correlated with miR-146a levels. Microdissection experiments revealed that miR-146a deficiency in hyperplastic MG thymuses was not due to GCs, but restricted to the GC-surrounding medulla, characterized by IRAK1 overexpression. We also showed higher c-REL and ICOS mRNA levels, and lower FAS mRNA levels, in GCs than in the remaining medulla, according to the contribution of these molecules in GC formation. By double immunofluorescence an increased proportion of IRAK1-expressing dendritic cells and macrophages was found in hyperplastic MG compared to control thymuses, along with GC immunoreactivity for c-REL. Interestingly, in corticosteroid-treated MG patients intra-thymic miR-146a and mRNA target levels were comparable to those of controls, suggesting that immunosuppressive therapy may restore the miRNA levels. Indeed, an effect of prednisone on miR-146a expression was demonstrated in vitro on peripheral blood cells. Serum miR-146a levels were lower in MG patients compared to controls, indicating dysregulation of the circulating miRNA. Our overall findings strongly suggest that defective miR-146a expression could contribute to persistent TLR activation, lack of inflammation resolution and hyperplastic changes in MG thymuses, thus linking TLR-mediated innate immunity to B cell-mediated autoimmunity. Furthermore, they unraveled a new mechanism of action of corticosteroids in inducing control of autoimmunity in MG via miR-146a.